PENGARUH PENAMBAHAN BUBUK UDANG REBON (Acetes Erythaeus) TERHADAP KANDUNGAN GIZI DAN DAYA TERIMA MENU PEMBERIAN MAKANAN TAMBAHAN (PMT) BALITA DI POSYANDU - Anis Abdul Muis; Uun Kunaepah; Alina Hizni; Priyo Sulistiyono (Jurnal Ilmu dan Teknologi Kesehatan, 2017)
The proportion of underweight children and stunting increased between 2007-2013. Underweight increased from 18.4% to 19.6% and stunting increased from 36.8% to 37.2% (Ministry of Health, 2013). Less food intake, the economic capacity of families and the lack of food cheap source of animal protein available and can be consumed by children under five is the cause of the problem. Small Shrimp (Aceteserythraeus) contains high protein and calcium, but not yet utilized optimally for nutritional improvement. This study aims to determine the acceptability of infants in food supplementary added Shrimp Powder (SP).This type of research is the experiment, with the design Randomised Control Trial (RCT) in the form of the acceptance test with the addition Shrimp Powder (SP) of menu food supplementary in infants at posyandu. Sampling RW.09 Village Kesunean Cirebon purposive sampling in the coastal areas with a high prevalence of malnutrition. A total sample of 60 toddlers of 30 toddlers and 30 toddlers control treatment, taken by systematic random sampling that meets screening criteria.Southwestern acceptance test results received of menu food supplementary with the addition Shrimp Powder 5% was slightly lower (79.9%) of the reception menu food supplementary without SP (87.5%) and showed no statistically significant differences(p= 0.215). Talam cake has received the highest power, then grits and steamed noodles. Shrimp powder at menu, 6,1-25,5kkal contributed to increasing energy, protein and calcium 1,3-5,5g 1,2-5,2mg per 100g food supplementary. SP can not be added in large quantities (± 5%), because it will affect the flavor and acceptability toddlers. To optimize SP contribution in improving the nutritional content of supplementary menu, then added in small portions (± 5%), but often